2012
DOI: 10.1002/pds.3310
|View full text |Cite
|
Sign up to set email alerts
|

Validation of acute myocardial infarction in the Food and Drug Administration's Mini‐Sentinel program

Abstract: Purpose To validate an algorithm based upon International Classification of Diseases, 9th revision, Clinical Modification (ICD-9-CM) codes for acute myocardial infarction (AMI) documented within the Mini-Sentinel Distributed Database (MSDD). Methods Using an ICD-9-CM-based algorithm (hospitalized patients with 410.x0 or 410.x1 in primary position), we identified a random sample of potential cases of AMI in 2009 from 4 Data Partners participating in the Mini-Sentinel Program. Cardiologist reviewers used infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 35 publications
3
64
2
Order By: Relevance
“…Interestingly, taken alone, the I20.0 code for unstable angina was relatively predictive of ACS but not very predictive of unstable angina, while the I21 code for acute MI was highly predictive of both ACS and STEMI/NSTEMI. Considering the code combinations, I21 with I24 had the highest PPV for ACS, yet the combination I20.0, I21 or I24 identified a notably greater number of validated cases while maintaining an acceptable PPV, similar to that of the validated ICD-9 codes for ACS identification [8,9]. Furthermore, although the PPV of I20.0 for unstable angina was much higher than that of I21, both identified a similar number of validated events.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, taken alone, the I20.0 code for unstable angina was relatively predictive of ACS but not very predictive of unstable angina, while the I21 code for acute MI was highly predictive of both ACS and STEMI/NSTEMI. Considering the code combinations, I21 with I24 had the highest PPV for ACS, yet the combination I20.0, I21 or I24 identified a notably greater number of validated cases while maintaining an acceptable PPV, similar to that of the validated ICD-9 codes for ACS identification [8,9]. Furthermore, although the PPV of I20.0 for unstable angina was much higher than that of I21, both identified a similar number of validated events.…”
Section: Discussionmentioning
confidence: 86%
“…Pharmacology has been performed for MI or ACS identification in North American databases that use ICD-9 (International Classification of Diseases and Related Health Problems, 9 th Edition) [8,9] as well as for MI in many European databases that use the more recent 10 th Edition (ICD-10) [10,11]. However, MI or ACS coding has not been evaluated in the French hospitalization database (Programme de M edicalisation des Syst emes d'Information, PMSI) that is the national database used by all hospitals in France.…”
Section: Fundamental and Clinicalmentioning
confidence: 99%
“…We directly assessed the clinical outcomes and not surrogate outcomes. We used validated algorithms to exclude patients with prevalent coronary heart disease (CHD) and to identify incident CHD outcomes 16 23. We included a set of carefully chosen CVD risk factors, in addition to demographics and use of health services, in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since not all AMI cases are identified with algorithms based on the principal diagnosis field only, a common study design dilemma is whether to also use other types of AMI administrative diagnoses (eg, secondary inpatient diagnoses and emergency department diagnoses) to identify AMIs. While the high PPV of principal inpatient diagnoses for AMI was confirmed by a prior validation study conducted within the SDD, to date, the validity of nonprincipal inpatient AMI diagnoses has not been assessed in the SDD. To provide researchers and other stakeholders with data on the validity of nonprincipal AMI diagnoses within the SDD, we report on the results of a chart validation study of potential AMI cases identified as part of a safety assessment of intravenous immune globulin (IGIV) products.…”
Section: Introductionmentioning
confidence: 96%